Evaluación de conocimiento sobre alimentación en los alumnos del Octavo Año de Básica del Colegio Bachillerato Daniel Álvarez Burneo 2013. - Espinoza Anaya, Luis Fabián (2013)
In assessing the level of knowledge about feeding the eighth year students of the College of Basic Bachelor " Daniel Alvarez Burnet 2013 " is a descriptive , cross-sectional , qualitative and quantitative with a universe of 400 students , taking a sample of 100 and generally apply a survey. Students are 50% male gender as female gender , the age group of 12 years ( 58 % ) and 11 and 13 years old ( 21 % ) each. The group investigated an average of 66% has a total ignorance about what are carbohydrates , lipids , proteins , vitamins , an average of 27.75 % a concept inadequate, when it has to do with the concept of a balanced diet for 44 % do not know the concept , 39% have an incomplete concept , and 17 % have an adequate concept . The 97 % do not consider fast -food meals suitable for physical activity , but consumed by 57 % every day , 2% and 1% unknown if deemed a suitable food . The 63 % consume snacks, every day, in what has to do with the intake of sweets to 42% of ingested every day which shows that in practice there is a high consumption of junk food by the group investigated . In regard to the protein energy foods consumed daily by 24% and the rest sporadically. Keywords : energy foods , fast food, snacks